Phytochemical screening and antibacterial activity of Azadirachta Indica leaves extract on common skin infection bacteria / Mohamad Azhar Azman ... [et al.] - Azman, Mohamad Azhar; Jaafar Sidek, Hamidah; Md Sharudin, Muhamad Shafizul; Nik Abdul Halim, Noor Aisyah; Raja Sahrom, Raja Muhammad Aliff Ariffin (Universiti Teknologi MARA, Perlis, 2016)
Skin infection is mainly caused by bacteria that are widely experienced by people around the world. The overuse of antibiotics has caused the development of resistant strains of bacteria. Thus, the need for a new natural antibiotics to provide treatment to the infection caused by these bacteria. Azadirachta indica is a very useful traditional medicinal plant and each part of the tree has various medicinal properties. This study was aimed at screening the active components and determining the antibacterial activity of the ethanolic crude extract of Azadirachta indica or commonly known as neem leaves on common bacteria that cause skin infection. The ethanolic crude extract of neem leaves was used for phytochemical screening and Kirby Bauer Disc Diffusion Assay. The result obtained from this study showed the presence of terpenoids, flavonoids, saponins, tannins, and alkaloids in the crude leaf extract. The antibacterial activity of the extract was tested on Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. The zone of inhibition of the Azadirachta indica crude extract against Escherichia coli showed the largest zone inhibition (21mm) compared to Staphylococcus aureus (16.5mm) and Pseudomonas aeruginosa (10mm). The inhibitory effect of the neem crude extract towards Escherichia coli also outperformed the inhibitory effect of the positive control of the ampicillin disc. Azadirachta indica crude extract may contain pharmacologically active constituents that may be responsible for its activity against S.aureus, E.coli, and P.aeruginosa that need further study. Therefore, the use of neem plant seems promising to be a potential antibacterial agent in treating skin infection caused by these bacteria.